OPTIMALISASI KINERJA TEKNIS PENGELOLAAN DAERAH IRIGASI JAMBO AYE DAN ALUE UBAY DI KABUPATEN ACEH UTARA - Rita Hartati; Marlinda Marlinda (Universitas Teuku Umar, 2019)
This study of research is to optimize and evaluate the technical performance of irrigation management in Jambo Ayen and Alue Ubay Irrigation Area in North Aceh District, so that the existing water resources system and the advantages of the two irrigation areas can be known. The experimental design used in this study is by literature study, and secondary data collection at several agencies. The results of this study indicate that the optimization of the average value of total efficiency ratio of water demand volume to water intake volume in Jambo Aye Irrigation Area is 81% and Alue Ubay 69%. Optimization of relative water supply in Jambo Aye irrigation area shows an average value of 2.82, irrigation area of Alue Ubay 2.33. The irrigation areas of Jambo Aye and Alue Ubay have average RPPA values with good category, that is 0.8-1.1. the indicator of maintenance of building effectiveness in Irrigation Area of Jambo Aye and Alue Ubay is 1. So it can be concluded that the optimization of the mean value of the total efficiency ratio of the volume of water demand to the volume of air intake is obtained to exceed the standard value of the technical irrigation network level.